Auction as a Method of Privatization of State Property - Imomniyozov Doniyor Bakhtiyorovich (Scientific Trends, 2024)
At the heart of the privatization issue is the need for transparency. Auctions naturally provide this transparency. Unlike direct sales, where prices can be negotiated behind closed doors, auctions are open and competitive. This openness ensures maximum financial return to the government by securing the highest possible price for its assets. When considering the privatization of public property through auctions, it is important to choose an auction format that ensures transparency, maximizes revenue, and is fair to all participants. There are several auction formats available, each with its own advantages and potential disadvantages. From this point of view, this article discusses the features of auction sales, their types, advantages and some disadvantages.
Keywords: State property, privatization, auction, tender, transparency, English auction format, Dutch auction, electronic auction, cybersecurity, transactions.